2020
DOI: 10.1021/acs.chemrestox.9b00477
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous Silica Nanoparticles at Predicted Environmentally Relevant Concentrations Cause Impairments in GABAergic Motor Neurons of Nematode Caenorhabditis elegans

Abstract: Available safety evaluations regarding mesoporous silica nanoparticles (mSiNPs) are based on the assumption of a relatively high exposure concentration, which makes the findings less valuable in a realistic environment. In this study, we employed Caenorhabditis elegans (C. elegans) as a model to assess the neuronal damage caused by mSiNPs at the predicted environmentally relevant concentrations. After nematodes were acute and prolonged exposed to mSiNPs at concentrations over 300 μg/L, locomotion degeneration,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…SiNPs induced the premature aging phenotype of C. elegans by accumulating insoluble proteins and amyloid-like proteins and reducing pharyngeal pumping ( Scharf et al, 2013 , Scharf et al, 2016 ). This toxicity mechanism is also supported by Liang et al (2020) , who demonstrated that the high exposure concentration of mesoporous silica nanoparticles induced neurotoxicity in C. elegans nematodes. The toxicity of nanoparticles is not a species-specific ( Hamed et al 2019 ); hence, these findings on C. elegans may contribute to explain our results on M. incognita .…”
Section: Discussionmentioning
confidence: 56%
“…SiNPs induced the premature aging phenotype of C. elegans by accumulating insoluble proteins and amyloid-like proteins and reducing pharyngeal pumping ( Scharf et al, 2013 , Scharf et al, 2016 ). This toxicity mechanism is also supported by Liang et al (2020) , who demonstrated that the high exposure concentration of mesoporous silica nanoparticles induced neurotoxicity in C. elegans nematodes. The toxicity of nanoparticles is not a species-specific ( Hamed et al 2019 ); hence, these findings on C. elegans may contribute to explain our results on M. incognita .…”
Section: Discussionmentioning
confidence: 56%
“…This organism has been reported to be used in toxicological studies of different nanomateirals, including carbon-based nanoparticles and quantum dots [14,16]. Meanwhile, the number of applications of C. elegans in assessing nanomaterials in the nervous system, especially adverse morphological changes of neurons, is increasing [17][18][19][20]. Therefore, in this study, the neurotoxicity of N-GQDs was assessed in this animal model and we focused on the adverse effects of N-GQDs in different types of neurons.…”
Section: Introductionmentioning
confidence: 99%